Relation with environmental education classes field and the content of biology in school - Lima, Renato Abreu; Braga, Andrina Guimarães Silva (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The research aimed to analyze the relationship of field classes with the formal content of Sciences with the high school students of a private school in Porto Velho-RO attending high school in two shifts. The aim of the intervention was to identify elements that indicate changes in students’ views on the environment, as well as discussing the importance of field trip for learning them. After subsidize students with basic knowledge in the classroom, an output field was performed in the Environmental Police Battalion (BPA), in the municipality of Candeias do Jamari, which is a region of special interest for conservation and environmental protection, as well thematic areas such as work related to water, land use, riparian vegetation, biomass, sustainability and preservation of springs. In BPA, runs the Recovery Centre for Wild Animals (CRAS) and the Environmental Education Center (ARC) which conducts environmental awareness and orientation activities. From the interaction with students in environmental issues, it was considered that there was a significant evolution in the way we perceive the environment and its influence on the same. Field work for some content improved learning because the student put directly in touch with your object of study.